In situ preparation of polyimide/titanium carbide composites with enhanced dielectric constant. Issue 1 (12th August 2014) - Weng, Ling; Xia, Qian‐shan; Yan, Li‐wen; Liu, Li‐zhu; Sun, Zhi
Abstract : A series of polyimide/titanium carbide (PI/TiC) composites with different TiC contents were prepared using the ultrasonic dispersion and in situ polymerization method. Atomic force microscopy (AFM), X‐ray diffraction (XRD), scanning electron microscope (SEM), mechanical, and electrometer were used to characterize the structure and properties of the obtained composites. The morphological study of composites by AFM and SEM showed that TiC particles had a homogeneous dispersion in polyimide matrix with nanoscale at low filler dosage (≤10% volume content). X‐ray diffractions (XRDs) indicated that the doping of TiC slightly reduced the packing density of polyimide and destructed the aggregation structure of polyimide molecules. Experimental results showed that the obtained PI/TiC composites exhibited appropriate mechanical properties and moderate electric breakdown strength. Dielectric investigation evidenced that the dielectric constant and the dielectric loss of these composites increased with the increase of the volume fraction of TiC particles. The composite with 20 vol% TiC particles showed a highest dielectric constant of 37 while retaining an appropriate dielectric loss of 0.026, as compared with the dielectric constant (3–4) of neat polyimide resin. In addition, the dielectric properties of the composites displayed good stability within a wide range of frequency. The results of this work demonstrate the potential use of a PI/TiC composite film in an embedded capacitor. POLYM. COMPOS., 125–130, 2016. © 2014 Society of Plastics Engineers